Find the general solution of the equation.

\begin{eqnarray} \tan \left(x+\frac{\pi }{3}\right)+3\tan \left(x-\frac{\pi }{6}\right)=0\\ \end{eqnarray}

The answers in my textbook are $n\pi $ and $n\pi +\frac{\pi }{3}$.

Previously, I compute the similar questions by using the following operations :

\begin{eqnarray} \\\tan 3x&=&\cot 5x\\ \\\tan 3x&=&-\tan \left(\frac{\pi }{2}+5x\right)\\ \\\tan 3x&=&\tan \left(-\frac{\pi }{2}-5x\right)\\ \\3x&=&-\frac{\pi }{2}-5x\\ \\8x&=&n\pi -\frac{\pi }{2}\\ \\x&=&\frac{n\pi }{8}-\frac{\pi }{16}\\ \end{eqnarray}

But now there is a 3 in front of the second tan.

What should I do?

I do not know whether my method is correct. If you have any other methods, would you mind telling me the methods?

Thank you for your attention.

Update 1 : Found one of the answers, are my operations correct? enter image description here

  • $\begingroup$ Is your question correct? The question seems likely than $tan(x+\pi/3)=3tan(x-\pi/6)$ $\endgroup$ – MS.Kim Oct 6 '13 at 12:18
  • $\begingroup$ Thx, the question now is correct. $\endgroup$ – Casper Oct 6 '13 at 12:24

If we assume that your question is to solve the equation $tan(x+\pi/3)+3tan(x-\pi/6)=0$. if we let $A=x+\pi/3, B=x-\pi/6$, then $A-B=\pi/2$, so we can transform the term $tanA$ to $tan(\pi/2+B)$.

and because $tan(\pi/2+B) = -cotB$, the equation will be $-cotB+3tanB=0$, $tan^2B=1/3$ so the general solution of $B=x-\pi/6=n\pi+\pi/6$ or $n\pi-\pi/6$

so $x=n\pi +\pi/3$ or $n\pi$


The solution is given as follows.

enter image description here

I don't know how to use spoiler for a block of code.

\tan (x+\frac{\pi}{3}) + 3\tan (x-\frac{\pi}{6})=0\\
\tan (x+\frac{\pi}{3}) = 3\tan (\frac{\pi}{6}-x)\\
\frac{\tan x + \tan \frac{\pi}{3}}{1-\tan x \tan \frac{\pi}{3}} = 3\frac{\tan \frac{\pi}{6} -\tan x}{1+\tan \frac{\pi}{6}\tan x}\\
\frac{\tan x + \sqrt 3}{1-\sqrt 3\tan x } = 3\frac{\frac{\sqrt 3}{3} -\tan x}{1+\frac{\sqrt 3\tan x}{3}}\\
\frac{\tan x + \sqrt 3}{1-\sqrt 3\tan x } = \frac{ \sqrt 3 -3 \tan x}{1+\frac{\sqrt 3\tan x}{3}}\\
\frac{\tan x + \sqrt 3}{1-\sqrt 3\tan x } = \frac{ \sqrt 3 -3 \tan x}{1+\frac{\sqrt 3\tan x}{3}}\times\frac{3}{3}\\
\frac{\tan x + \sqrt 3}{1-\sqrt 3\tan x } = \frac{ 3\sqrt 3 -9 \tan x}{3+ \sqrt 3\tan x}\\
(1- \sqrt 3\tan x) (3\sqrt 3 -9 \tan x) = (\tan x + \sqrt 3)(3+ \sqrt 3\tan x)\\
3\sqrt 3 -9\tan x -9\tan x +9\sqrt 3\tan^2x = 3\tan x +\sqrt 3\tan^2 x +3\sqrt 3 +3\tan x\\
8\sqrt 3\tan^2 x  -24 \tan x=0\\
\sqrt 3\tan^2 x -3\tan x=0\\
\tan x (\sqrt 3 \tan x -3)=0\\
\tan x =0 \text{ or } \sqrt 3 \tan x -3 =0\\
\tan x=0 \text{ or } \tan x =\sqrt 3\\
x=n\pi \text{ or } x=\frac{\pi}{3}+n\pi

  • $\begingroup$ =口= This operation must take so much time when during exam...Is it the best way? $\endgroup$ – Casper Oct 6 '13 at 13:42
  • $\begingroup$ @CasperLi: Not much even though you use LaTeX during the exam. :-) $\endgroup$ – kiss my armpit Oct 6 '13 at 13:44
  • $\begingroup$ Are there any fast methods to input math/LaTeX? ~.~ $\endgroup$ – Casper Oct 6 '13 at 13:53
  • $\begingroup$ @CasperLi: It depends on the text editor you are using. If there is a shortcut key for each macro then you can type much faster. But I think the important point is your typing speed. :-) $\endgroup$ – kiss my armpit Oct 6 '13 at 13:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.